Reforma de biogás para produção de hidrogênio usando catalisadores tipo perovskitas a base de lantânio e níquel, dopados com cério - Xavier, Thiago Padovani (2011)
In the present study, the behavior of La1-xCexNiO3 (x = 0; 0.05 and 0.10) perovskite-type oxides catalysts was investigated, acting as catalysts, in reactions of dry reforming of methane (DRM) and biogas reforming (BR). The catalysts were synthesized by sol-gel method (or citrate) and by combustion with urea. Later, they were structurally evaluated and studied on the catalytic performance. The synthesized perovskite-type oxides were characterized by X-ray diffraction, nitrogen adsorption temperature programmed reduction and thermal gravimetric analysis. The catalysts showed low values of specific area (< 10 m2 g-1). The LaNiO3 phase present in all the calcined samples was converted into La2O3, Ni0 and La(OH)3 after reduction, keeping the phase CeO2 in the doped samples with cerium. It was observed more evident La(OH)3 phase in the samples synthesized by combustion method. The average crystallite sizes, on the main stage LaNiO3, remained between 13 to 17 nm. La0,90Ce0,10NiO3 synthesized by combustion had the lowest average crystallite size whereas La0, 95Ce0,05NiO3 and La0,90Ce0,10NiO3 synthesized by sol-gel method has the highest value. The sol-gel method produced NiO grains (20-25 nm) smaller than those produced by the combustion method (31 - 38 nm). But for all samples is observed a decrease in average Ni0 grain sizes after reduction. In the samples synthesized by combustion method the mean Ni0 crystallite size were similar (20, 19 and 21 nm), whereas the values increased with Ce addition (13 21 nm) in the samples synthesized by sol-gel method. All samples with 1:9 dilution (catalyst/ inert SiC) were active, stable and resistant to deactivation by coke deposition after 24 h of DRM and BR reactions, but with molar ratio H2/CO < 1. The La0,90Ce0,10NiO3 catalyst synthesized by sol-gel method, with 1:1 dilution (catalyst/ inert SiC) showed the greatest resistance to the carbon formation (1,06 mg Carbon / gcat h). The catalysts synthesized by the combustion method, when 1:9 diluted, showed TOFCH4 values between 13 - 16 in the DRM and between 15 - 19 in BR, with molar ratio H2/CO next 1. The catalysts synthesized by combustion method, with 1:1 dilution (catalyst/inert SiC) were more active (TOFCH4 8 13 h-1) in BR reaction than the catalysts synthesized by sol-gel method (TOFCH4 3 4 h-1). The lower values for the stoichiometric H2/CO <1 indicate favoring the reverse reaction of water-gas shift in catalytic tests, supported by the fact that higher CO2 conversion in all reactions usin catalysts with 1:9 dilution. There was a molar ratio H2/CO increase in the RB, especially when used as the catalyst with 1:1 dilution (catalyst/inert SiC), indicating that reverse water-gas shift reaction is less favored when feed CH4: CO2 = 2 and using a larger amount of catalyst.